The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/pace.13787
|View full text |Cite
|
Sign up to set email alerts
|

Pacemaker pocket infection: Innovative conservative treatment in elderly patients with no signs of systemic infection

Abstract: Background The gold standard to treat cardiovascular implantable electronic devices (CIEDs) infections is the complete system removal. The aim of this retrospective analysis is to assess the feasibility and safety of an alternative conservative surgical system revision approach, to be applied in elderly patients who refused the extraction procedure, in case of no signs of systemic infection. Methods Between May 2009 and January 2019, we performed system revision of 25 patients (15 men and 10 women, median age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Poller et al, Satsu et al, McGarry et al, and Zheng et al have stated that the negative pressure drainage system is effective for pacemaker pocket site infections in the long term [21,[27][28][29]. In a study of 25 case series by Bisignani et al no recurrence was observed in 24 of the patients during the 24-month follow-up period after local revision, debridement, and reimplantation [23]. A total of 33 patients were included in the study by Cassagneau et al The patients were divided into three groups according to the clinical characteristics of the pocket site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poller et al, Satsu et al, McGarry et al, and Zheng et al have stated that the negative pressure drainage system is effective for pacemaker pocket site infections in the long term [21,[27][28][29]. In a study of 25 case series by Bisignani et al no recurrence was observed in 24 of the patients during the 24-month follow-up period after local revision, debridement, and reimplantation [23]. A total of 33 patients were included in the study by Cassagneau et al The patients were divided into three groups according to the clinical characteristics of the pocket site.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Bisignani et al of 25 cases in the elderly, no systemic infection or blood culture positivity was observed, but 24 of 25 patients had pacemaker pocket site infection with positive culture results. Re-infection was observed in only one patient [23]. According to the 2020 European Cardiac Rhythm Consensus Document, cardiac device infection was accepted if the site of infection was a pacemaker generator or lead protrusion, regardless of the results of the swab cultures [1][2][3][4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elsewhere, favorable outcomes of conservative treatment were reported in a case of pacemaker pocket infection by a 2-stage surgical revision technique with a continuous infusion of antibiotics. 7 In addition, long-term survival has been reported in cases of conservative treatment consisting of removing infected and necrotic tissue. 8 , 9 Our case is unique because pacemaker leads directly protruded from the chest epidermis owing to complete pocket defection and we were able to achieve long-term survival.…”
Section: Discussionmentioning
confidence: 99%